THE USE OF ACTION MOVIE TRAILER IN TEACHING NARRATIVE TEXT WRITING AT MAN 1 PONTIANAK - Muhammad Arif Nuryanto; Regina Regina; Yanti Sri Rezeki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract: The aim of this study was to find out the empirical evidence about the effectiveness and the effect size of the use of action movie trailer towards students’ narrative text writing at the tenth grade students of MAN 1 Pontianak.  The method of this study was quantitative method. This study used quasi experimental design with pre-test and post-test design approach. The population of this study was 299 tenth grade students of MAN 1 Pontianak in academic year 2016/2017. By using simple random sampling, the researcher took two classes as the samples of this study. The samples were XMIPA 1 as the experimental class which was taught by using action movie trailer and XMIPA 2 as the control class which was taught without using action movie trailer. The experimental class consisted of 35 students and the control class consisted of 36 students. Pre-test was given before the implementation of the treatment and post-test was given after the treatment to both groups. The instrument used in this study was writing test in which the students were asked to write a narrative text. The results of this study showed that action movie trailer was effective and the criteria of the effect size was categorized strong. As the result, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Hence, it was concluded that action movie trailer is strongly effective in teaching writing of narrative text. Keywords: Action Movie Trailer, Writing, Narrative Text